An EU-wide Nuclear Power Tax: Rationale and Possible Effects - Dellinger, Fanny; Schratzenstaller, Margit (International Journal of Energy Economics and Policy, 2018)
Nuclear power plays an important role in Europe’s energy mix today. Considering the manifold environmental and health hazards related to all phases of nuclear power production, which may cause considerable negative externalities, it is remarkable that the whole issue of using taxes as instruments to internalise the externalities associated with nuclear power is completely neglected in the literature. The paper provides a rationale for taxing nuclear power which is based on an analysis of its social costs and of potential windfall profits for the nuclear industry generated by EU policies. After giving an overview over existing nuclear taxes in the nuclear power generating EU Member States, we elaborate the case for channeling revenues from a nuclear power tax into the EU budget as sustainability-oriented tax-based own resource. We also estimate the potential revenues from an EU-wide nuclear power tax. Keywords: nuclear power tax; sustainability-oriented taxation; EU system of own resources JEL Classifications: H23, H87, Q58 DOI: https://doi.org/10.32479/ijeep.7064